2016
DOI: 10.3233/ip-150366
|View full text |Cite
|
Sign up to set email alerts
|

Local e-government Benchlearning: Impact analysis and applicability to smart cities benchmarking

Abstract: Abstract. We claim that local e-services benchmarking studies summarized in indexes do little to enhance city managers' and academics' understanding of actual e-government performance, or to improve the e-services offered by cities. We undertook a different benchmarking approach, focused on learning best practices among cities, in late 2008 and early 2009. A benchlearning methodology (BLM) was developed, and a pilot study with 15 European cities was carried out. In this paper, we present the actual impact of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Application areas of smart cities are smart health, people, traffic, waste management, parking, government and industry. Cisco was the first company which proposed a smart city's model applied in Dubai components such as economy, mobility, government, environment and people [45]. The sustainability of the various urban tasks must depend primarily on perfect and complete information infrastructure.…”
Section: Dimensions and Applications Of Smart Citiesmentioning
confidence: 99%
“…Application areas of smart cities are smart health, people, traffic, waste management, parking, government and industry. Cisco was the first company which proposed a smart city's model applied in Dubai components such as economy, mobility, government, environment and people [45]. The sustainability of the various urban tasks must depend primarily on perfect and complete information infrastructure.…”
Section: Dimensions and Applications Of Smart Citiesmentioning
confidence: 99%
“…Primary research showed the post-GDPR influence in cities such as Porto, Amsterdam, London, Vienna, Milan, Barcelona, and Glasgow. Unlike previous research and publications that focused on benchmarking factors [130,131], this article directly approached city representatives/strategists by asking them to unfold their understanding around digital rights. Insofar as previous research revealed the need for enlarging the ecosystem of e-services in city administration to include citizens, the third sector, entrepreneurs, and activists; this article, by using recent research on Penta Helix model [96], not only included these stakeholders in the semi-structured questionnaire but also explored digital rights through these multistakeholder lenses.…”
Section: Discussionmentioning
confidence: 99%
“…This is a more qualitative approach and has been picked up in research on e-government, were the results from benchmarks are put into practice: via learning and sharing of experiences, as seen in the case of providing assistance to developing countries (Kromidha, 2012). Another study developed a benchlearning methodology to help improve e-services in local government, and found benchlearning and its emphasis on learning and sharing experiences benign for improving e-services (Batlle-Montserrat et al, 2016). This crucial point of being able to learn from benchmarks, is succinctly expressed by Ammons (1999, pp.…”
Section: E-government and The Concept Of Benchmarkmentioning
confidence: 99%